ANALISIS INTENSI WAKIF GEN Y DALAM GERAKAN DIGITAL BERWAKAF UANG ATAU MELALUI UANG DI INDONESIA - Meutia Rahma; Mukhamad Najib; Imam Teguh Saptono (Jurnal Aplikasi Bisnis dan Manajemen (JABM), 2021)
The purpose of this study is to identify the characteristics of wakif gen Y in waqf activities and analyze what factors influence the intention of wakif gen Y in the use of digital payment technology to encourage the digital movement of cash waqf and waqf through money in Indonesia. In general, this research is conducted qualitatively through descriptive and quantitative analysis through structural equation modeling (SEM) analysis. The number of samples studied was 160 wakif gen Y. The results showed that all the variables studied were performance expectancy (PE), effort expectancy (EE), social influence (SI), facilitating condition (FC), hedonic motivation (HM), price value (PV), habit (HT), and perceived security (PS) have a significant influence on behavioral intention (BI) wakif gen Y in encouraging the use of digital payment technology for cash waqf payments. The biggest factor is habit with a value of t count 12.93, and the standardized coefficient is 0.59. The next factor that has a significant effect on priority is performance expectancy (PE). Keywords: digital payment, intention, cash waqf, waqf through money, wakif gen Y